The Native Communities of the Peruvian Amazon and the Accomplishment of Subsections "C" and "D" from the Article 10 of The Convention on Biological Diversity. Similar Situations in The European Union. - Rueda Romero, Paulino Saúl (2015)
In the United Nations conference on environment and development, signed the Convention on Biological Diversity, which obliges the signatory States to combat the extinction of species throughout the world. Its executive secretary said: "the services that nature offers us are free, but the man has a deep unconsciousof what he represents their destruction [...] If humanity does not brake to the degradation of biodiversity, the legacy for future generations will be mortgaged […] must have the courage to look our children in the eye and admit failure [...] admit that we continue losing biodiversity at an unprecedented pace, we are mortgaging their future". Words that initialed by premonitions future about the treatment of the extinction of a large part of the existing biodiversity, that if we do not a treatment, their destruction would speed up and we would be going against the new scheme of sustainable development.In this paper, I analyze and discuss from the perspective of